Leaching of tin from waste Pb-free solder in hydrochloric acid solution with stannic chloride - Kim, S.; Lee, J.; Yoo, Kyoungkeun (Elsevier, 2016)
A hydrochloric acid (HCl) leaching process with stannic chloride (SnCl4) was proposed to leach Sn from waste Pb-free solder containing Sn, Ag, and Cu, where the oxidant stannic ion (Sn4 +) oxidizes Sn metal into stannous ion (Sn2 +). When Sn reagent-grade powder was leached in HCl solution with SnCl4, the leaching efficiency of Sn increased rapidly and the oxidation-reduction potential decreased with leaching time. In the leaching tests of Pb-free solder, the effect of factors such as the agitation speed, HCl concentration, pulp density, and temperature on the leaching behaviors of metals was investigated. The leaching efficiencies of Sn increased rapidly in the beginning of leaching with increasing agitation speed, HCl concentration, and temperature. The difference in the leaching efficiencies was negligible after 90 min under the following conditions: HCl concentration of 1–3 kmol m- 3, agitation speed of 300–600 rpm, and temperature of 50 °C or 70 °C. Although the pulp density was increased from 1% to 2%, the Sn concentration dissolved did not exceed 10,500 g m- 3 because of the lack of oxidant, and the increase in the initial concentration of Sn4 + as the oxidant could accelerate the leaching of Sn. A Sn leaching efficiency of greater than 99% was achieved in 1 kmol m- 3 HCl with 10,000 g m- 3 Sn4 + at 400 rpm and 50 °C with 1% pulp density within 90 min. Ag was not detected in any of the leaching tests. Although the leaching solution contained 24.5 g m- 3 of Cu, the addition of Sn powder was successful in removing Cu from the solution via a cementation reaction. Thus, a Sn leaching solution was successfully obtained from Pb-free solder via HCl leaching with SnCl4.